PELAKSANAAN FUNGSI PENGADILAN AGAMA DALAM MENGENDALIKAN TINGGINYA TINGKAT PERCERAIAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI PENGADILAN AGAMA RENGAT TAHUN 2019 - Imeldalius SH., MH (STIA Indragiri, 2019)
AbstractMarriage is a spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Godhead and divorce is something that is hated by God, although it is permissible, for that the role of the court Religion is very important in reducing the high divorce rate, because the Religious Courts through Judges can carry out the principle of divorce making it difficult and seek parties to carry out mediation in advance so that divorce does not occur so that the households of those who wish to divorce can be saved.